Minimally invasive mini-thoracotomy access as a surgical method in state-of-the-art treatment of single-vessel coronary heart disease - Edin Kabil; Nermir Granov; Ilirijana Haxibeqiri-Karabdić; Sanja Grabovica; Ermina Mujičić; Slavenka Štraus; Bedrudin Banjanović; Muhamed Djedović (Medicinski glasnik, 2022)
Aim: To compare outcomes of two different surgical techniques of coronary artery bypass grafting (CABG) for treating isolated left anterior descending (LAD) coronary artery disease by full median sternotomy technique vs. minimally invasive approach via left anterior mini-thoracotomy. Methods: This retrospective, observational study, which included 61 elective patients, was conducted at the Clinic for Cardiovascular Surgery of the Clinical Centre of the University of Sarajevo in the period from June 2019 to January 2022. Patients were divided in two groups according to the operative technique used, the sternotomy CABG group of 30 patients where the access considered full median sternotomy, and the minimally invasive CABG group where left anterior mini-thoracotomy was performed. The groups were compared by previously defined primary and secondary clinical postoperative outcomes. Results: Out of 61 patients, the majority was males, 50 (82%). The analysis of the outcomes of the minimally invasive CABG surgery showed significantly shorter operative times (p=0.001), less postoperative drainage (p=0.001) and transfusion requirements, shorter mechanical ventilation duration (p=0.0001), low major adverse cardiac and cerebrovascular events rates, as well as shorter Intensive Care Unit stay days with mean of 3.3±1.442 days (p=0.025), but no total hospital stay days with mean of 6.7±1.832 days (p=0.075) compared to sternotomy CABG group. Conclusion: Minimally invasive approach for CABG surgery in treating isolated single vessel LAD disease, together with the fasttrack protocol, offers a reasonable alternative to full median sternotomy, leading to faster patients’ overall recovery and improving the quality of life.
Keywords: anaesthesia; revascularization; cardiac surgery